Pengertian dan Syarat Profesi Keguruan - Eni Sri Wahyuni; Nur Resky Al Hijrah Syam; Srwiulan; Takdirmin (STKIP Subang, 2026)
The teaching profession is a specialized field that requires specific expertise and legal recognition. This non-empirical article aims to examine the definition and requirements of the teaching profession based on a conceptual literature review of sources published in the last five years. The method used is a conceptual literature review involving systematic searching, selection, and synthesis of relevant sources. The findings indicate that the teaching profession is not merely a job but a vocation that demands pedagogical, personal, social, and professional competencies, supported by official certification and adherence to a code of ethics. This article emphasizes that meeting these requirements is essential to ensure the quality of national education. Keywords: teaching profession, teacher requirements, education, professionalism.